Ghrelin enhances tubular magnesium absorption in the kidney - Nie, Mingzhu; Zhang, Jing; Bal, Manjot; Duran, Claudia; An, Sung Wan; Zigman, Jeffrey M.; Baum, Michel; Hiremath, Chitkale; Marciano, Denise K.; Wolf, Matthias T. F. (Frontiers in Physiology, 2024)
In animal studies mimicking bariatric procedures, bone disease together with decreased serum levels of Ca2+, Mg2+ and the gastric hormone Ghrelin were described. Ghrelin is an acylated peptide that regulates metabolism by binding to and activating the growth hormone secretagogue-receptor (GHSR) which is also expressed in the kidney. We tested the hypothesis that Ghrelin-deficiency contributes to osteoporosis via reduced upregulation of the renal calcium channel TRPV5 and the magnesium channel TRPM6. After Ghrelin exposure, whole-cell current density did not change for TRPV5 but increased for TRPM6 in a dose-dependent fashion. We confirmed the stimulatory role of Ghrelin towards TRPM6 current density by applying the Ghrelin-mimetic (D-Trp7, Ala8,D-Phe10)-α-MSH (6-11) amide without and with the GHSR antagonist (D-Lys3)-GHRP6. As GHSR initiates downstream signaling via protein kinase A (PKA), we found that the PKA inhibitor H89 abrogated TRPM6 stimulation by Ghrelin. Similarly, transfected Gαs, but not the Gαs mutant Q227L, nor Gαi2, Gαq, or Gα13 upregulated TRPM6 current density. In microdissected TALs and DCTs similar levels of GHSR mRNA were detected. In contrast, TRPM6 mRNA was highly expressed in the DCT and also detected in the TAL. Immunofluorescent studies using reporter GHSR-eGFP mice showed a strong eGFP signal in the TAL but surprisingly displayed no eGFP signal in the DCT. In 3-, 6-, and 9-month-old GHSR-null and WT mice, baseline serum magnesium was not significantly different, but 24-hour urinary magnesium excretion was elevated in 9-month-old GHSR-null mice. In calorically restricted GHSR-null mice, we detected excess urinary magnesium excretion and reduced serum magnesium levels compared to WT mice. In kidneys from calorically restricted WT compared to GHSR-null mice gene expression of magnesiotropic genes were upregulated. In conclusion, our studies show that Ghrelin stimulates TRPM6 via GHSR and Gαs-PKA signaling. The murine studies are consistent with Ghrelin-GHSR signaling inducing reduced urinary magnesium excretion, particularly in calorically restricted mice when Ghrelin levels are elevated. This effect may be mediated by Ghrelin-upregulation of TRPM6 in the TAL and/or upregulation of other magnesiotropic genes. We postulate that rising Ghrelin levels with hunger contribute to increased renal Mg2+ reabsorption to compensate for lack of enteral Mg2+ uptake.